Study on solubility of surfactants in water by fiber optic spectrophotometer - Nagy, Roland; Sallai, Rubina; Bartha, Laszlo; Vago, Arpad (Publishing House of Lviv Polytechnic National University, 2015)
The vegetable oil based emulsifiers represent a remarkable potential in the petroleum industry. In the chemical enhanced oil recovery (EOR) the application of the nonionic surfactants have a growing importance as a biodegradable type additive. The aim of our work is to prepare a simple and rapid instrumental measurement that could be used in the industrial practice and would be suitable to control the water solubility of the surfactants produced for EOR technologies by using of the available AvaSpec fiber optic spectrophotometer. Показано, що емульгатори на основі олій є значним потенціалом у нафтовій промисловості. Застосування нейоногенних поверхнево-активних речовин (ПАР) при видобутку нафти набуває все більшого значення як додатку біодегредабельного типу. Розроблено прості та швидкі методи вимірювання, які можуть бути використані в промисловій практиці і придатні для контролю розчинності у воді ПАР, отриманих для вищевказаного процесу. Контроль здійснюється за допомогою волоконно-оптичного спектрофотометра AvaSpec.
Дослідження розчинності поверхнево-активних речовин у воді за допомогою волоконно-оптичного спектрофотометру
Keywords: surfactant; solubility; spectrophotometer; HLB value; поверхнево-активна речовина; розчинність; спектрофотометр; гідрофільно-ліпофільний баланс